Adaptation to Social Change and Urbanization: Community-Based Health Strategies for Public Health - Andarmoyo, Sulistyo; Davis, Olivia; Green, Jessica (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Social change and rapid urbanization have profoundly impacted public health systems, presenting challenges such as rising health disparities, increased prevalence of non-communicable diseases, and the strain on healthcare infrastructure. In response to these challenges, community-based health strategies have gained traction as effective approaches to improving public health outcomes. This research explores the role of community-based health strategies in adapting to the demands of social change and urbanization, with a focus on their impact on health equity, accessibility, and health system resilience. A mixed-methods approach was employed, combining quantitative data from health surveys and qualitative interviews with community leaders and healthcare providers to assess the effectiveness of community-driven health initiatives. The findings indicate that community-based programs significantly improved health outcomes, especially in urban areas facing overcrowding and limited access to healthcare. These programs enhanced health literacy, preventive care, and collaborative efforts between communities and healthcare providers. The study concludes that community-driven health models offer a sustainable solution to public health challenges in rapidly urbanizing regions. The research highlights the importance of integrating these strategies into urban health policy to ensure a more resilient and equitable healthcare system.